Lateral Organ Boundaries Domain16 and 18 Act Downstream of the AUXIN1 and LIKE-AUXIN3 Auxin Influx Carriers to Control Lateral Root Development in Arabidopsis. Issue 4 (9th June 2015) - Lee, Han Woo; Cho, Chuloh; Kim, Jungmook
Abstract : Two auxin influx carriers are required for auxin signaling that activates transcriptional control in lateral root development. Abstract: Several members of the Lateral Organ Boundaries Domain ( LBD ) /Asymmetric Leaves2-Like ( ASL ) gene family have been identified to play important roles in Arabidopsis ( Arabidopsis thaliana ) lateral root (LR ) development during auxin response, but their functional relationship with auxin transporters has not been established yet. Here, we show that the AUXIN1 (AUX1) and LIKE-AUXIN3 (LAX3) auxin influx carriers are required for auxin signaling that activates LBD16/ASL18 and LBD18/ASL20 to control LR development. The lax3 mutant phenotype was not significantly enhanced when combined with lbd16 or lbd18 . However, LBD18 overexpression could rescue the defects in LR emergence in lax3 with concomitant expression of the LBD18 target genes. Genetic and gene expression analyses indicated that LBD16 and LBD18 act with AUX1 to regulate LR initiation and LR primordium development, and that AUX1 and LAX3 are needed for auxin-responsive expression of LBD16 and LBD18 . LBD18:SUPERMAN REPRESSIVE DOMAIN X in the lbd18 mutant inhibited LR initiation and LR primordium development in response to a gravitropic stimulus and suppressed promoter activities of the cell cycle genes Cyclin-Dependent Kinase A1;1 and CYCLINB1;1 . Taken together, these results suggest that LBD16 and LBD18 are important regulators of LR initiation and development downstream of AUX1 and LAX3.